Global trade and food safety : winners and losers in a fragmented system - Wilson, John S., 1956- 1956- (Policy research working paper, 2001)
How food safety is addressed in the world trade system is critical for developing countries that continue to rely on agricultural exports. An analysis shows that adopting a worldwide standard of a toxin affecting nuts and grains could increase trade in these commodities by